Multi-purpose structured catalysts designed and manufactured by 3D printing - Anna Lind; Ørnulv Vistad; Martin Fleissner Sunding; Kari Anne Andreassen; Jasmina Hafizovic Cavka; Carlos A. Grande (Materials & Design, 2020)
This work presents an example of the design and manufacture capabilities that 3D printing can introduce in catalysis. A multi-purpose catalyst, with fast heat and mass transfer and low-pressure drop has been designed and manufactured by 3D printing. The novelty of the methodology is the combination of advanced techniques for accurate control on the micropore-level allied with a generic framework for the design of macropore and structural levels. The ability to design ordered macroporous should be combined with adequate and controllable implantation of surface functionalities. With this combination of advanced techniques for macro and micro-pore control, it is possible to produce catalysts that unlock traditional trade-off compromises between diffusion, pressure drop and heat transfer.To demonstrate this novel methodology, we have designed and 3D printed a cubic iso-reticular foam in AlSi10Mg. After producing the support, its entire internal area was anodized to high-surface alumina followed by Pt deposition. We have verified the reproducibility of this technique by manufacturing a catalyst for a demonstrator with 8 m length. The test reaction was oxidation of NO to NO2 with the main aim to accelerate this reaction for additional recovery of energy in the production of nitric acid. Keywords: 3D printing, Catalyst, Anodization, Process intensification, Diffusion, Heat transfer